Promoting Sports Practice in Persons with Hemophilia: A Survey of Clinicians’ Perspective - Giuseppe Lassandro (MDPI AG, 2021)
Historically, people with hemophilia have been warned to avoid physical activities as a possible cause of bleeding; however, currently, sport is considered necessary, especially in the developmental age, for providing a good quality of life. A survey was proposed to a group of hematologists and sports physicians working in Puglia, Italy, to explore their approach to physical activities for their patients with hemophilia and to obtain suggestions about possible interventions to promote the access of patients to sports. The survey was answered by 6 hematologists and 15 sports physicians. In total, 71% (about six patients/year/physician) of patients with hemophilia seen by sports physicians asked for counseling about sports, and 67% (about five patients/year/physician) actually practiced sports. On the other hand, only 31% (about 16 patients/year/hematologist) of patients asked hematologists questions on sports, and only 16% (about seven patients/year/hematologist) of patients with hemophilia and that were followed-up by hematologists practiced sports. The sports most often recommended to patients with hemophilia by physicians included swimming, athletics, tennis, running and gymnastics. According to hematologists, physical activity was very efficient in improving the quality of life of patients; stability of joints; their psychological, social and musculoskeletal wellbeing; and in reducing the risk of bleedings. On the other hand, physical activity was considered less important in all these areas by sport physicians. In conclusion, answers to this survey suggested that sports could be promoted among hemophilic patients by increasing the sports physicians’ knowledge about hemophilia and their special role in this area. In addition, interviewed clinicians were of the opinion that increased awareness of specific guidelines and clinical practice protocols among both hematologists and sports physicians could be beneficial. Finally, answers suggested that access to fitness certification should be facilitated.